Polyvinyl alcohol/silver electrospun nanofibers: Biocidal filter media capturing virus‐size particles. Issue 46 (16th July 2021) - Blosi, Magda; Costa, Anna Luisa; Ortelli, Simona; Belosi, Franco; Ravegnani, Fabrizio; Varesano, Alessio; Tonetti, Cinzia; Zanoni, Ilaria; Vineis, Claudia
Abstract: In response to the nowadays battle against SARS‐CoV‐2, we designed a new class of high performant filter media suitable to advance the facemask technology and provide new efficient widespread solutions against virus propagation. By means of the electrospinning technology we developed filter media based on polyvinyl alcohol (PVA) nanofibers doped with AgNPs combining three main performance requirements: high air filtration efficiency to capture nanometer‐size particles, low airflow resistance essential to ensure breathability and antimicrobial activity to inactivate aerosolized microorganisms. PVA/AgNPs electrospun nanofibers were produced by electrospinning the dispersion of colloidal silver into the PVA water solution. A widespread physicochemical characterization was addressed to the Ag colloidal suspension. The key functional performances of the electrospun nanofibers were proven by water stability, antibacterial activity, and filtration efficiency and pressure drop measurements performed under conditions representative of facemasks. We assessed a total bacterial depletion associated to a filtering efficiency towards nano‐aerosolized particles of 97.7% higher than required by the EN149 standard and a pressure drop in line with FFP1 and FFP2 masks, even at the highest filtration velocity. Such results pave the way to the application of PVA/AgNPs electrospun nanofibers in facemasks as advanced filtering media for protecting against airborne microorganisms. Abstract : The battle against SARS‐CoV‐2 requires affordable solutions to block virus propagation before infecting cells. Electrospinning is one of the promising technologies, providing patches (filter media) able to capture nanometer‐size particles and inactivate aerosolized microorganisms, if doped with antimicrobial ingredients, like Ag nanoparticles. In this work we produced PVA/Ag electrospun nanofibers and found high filtering efficiency, low air drop‐pressure and excellent antibacterial properties, making them optimum candidates to be incorporated in personal protective equipment face masks.